Assessment of salivary alpha amylase and mucin-4 before and after non-surgical treatment of peri-implant mucositis - Hajer A. Aldulaijan; Abeer S. Al-Zawawi; Marwa Y. Shaheen; Dena Ali; Darshan Devang Divakar; Amani M. Basudan (SpringerOpen, 2022)
Abstract Background The present study was based on the null hypothesis that there is no difference in clinicoradiographic parameters and whole salivary alpha amylase (AA) and mucin-4 levels before and after non-surgical mechanical debridement (NSMD) of patients with peri-implant mucositis (PM). The aim was to assess whole salivary AA and mucin-4 levels before and after treatment of PM. Methods Patients with PM (Group-1) and individuals without peri-implant diseases (Group-2) were included. Demographic data was collected and peri-implant modified plaque and bleeding indices (mPI and mBI, respectively), probing depth (PD) and crestal bone loss were measured at baseline. Levels of AA and mucin-4 were assessed in unstimulated whole saliva samples. All patients underwent full-mouth non-surgical periodontal therapy (NSPT) and NSMD; and clinical parameters and salivary biomarkers were re-assessed after 3 months. Level of significance was set at P < 0.01. Results Twenty-six and 32 individuals were included in groups 1 and 2, respectively. None of the participants had periodontitis. At baseline clinical periodontal parameters (PI [P < 0.001], GI [P < 0.001], clinical AL [P < 0.001] and PD [P < 0.001]) were significantly high in Group-1 than Group-2. At 3-month follow-up, there was a statistically significant reduction in clinical periodontal and peri-implant parameters (PI [P < 0.01], GI [P < 0.01], and PD [P < 0.01]) in Group-1 compared with their baseline values. At baseline, salivary AA levels were significantly high in Group-1 than Group-2 (P < 0.01). At 3-month follow-up, there was no significant difference in whole salivary AA levels among patients in groups 1 and 2. Conclusions The AA and mucin-4 levels are potential biomarkers for evaluation of peri-implant diseases including PM. Mechanical instrumentation continues to be the most predictable treatment option for the management of peri-implant diseases.